ANALISIS DAMPAK PEMBANGUNAN RUAS JALAN NASIONAL WAMENA-MULIA-SINAK - Jontor Nababan; Harmonis Rante; Dewi Ana Rusim (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
The basic infrastructure needs to be built in Papua is transportation, settlement and socio-economic infrastructure. Road infrastructure will open the isolation of a region so that it can interact and transact with other regions to meet each other's needs. Road construction certainly has positive and negative impacts on an area. The government, through the National Road Department, builds various road sections that connect regions in Papua. One of them is the Wamena-Mulia-Sinak section, which connects the Wamena, Sinak and Mulia areas. These three regions are still lagging behind other regions in Papua. This section of the road is built through mountains and ravines, so the route is quite extreme. This study aims to analyze the impacts that arise and regional developments in the area traversed by this section. The location of the research was carried out along the road and data analysis was carried out by qualitative methods. The results shown that the construction of roads brings positive benefits in the form of smoother and lower prices of basic commodities, shorter travel times, transportation reach the remote areas, ease transportation of building materials and opening the isolation between regions. The negative impact is related to the destruction of conservation areas and the declining quality of the environment. The areas traversed by this road segment is developing that marked by the growth of new settlements, the economy is moving forward and the increase in community social services